Digital Pakistan : A Business and Trade Assessment - Saez, Sebastian; Rizwan, Nadeem; van der Marel, Erik (World Bank, Washington, DC, 2020)
This report analyses the recent trends in Pakistani Information Technologies (IT) and InformationTechnologies enabled Services (ITeS), as well as obstacles confronted by firms. The authors assess the importance of trade costs as a barrier to services growth and development in Pakistan’s domestic market and to seizing the opportunities of global trade. The report also aims to understand and examine the impact of obstacles (i.e., trade costs) confronted by firms. These obstacles increase the costs of selling services and may reduce capacity to compete both in the local market (Pakistan) as well as overseas (exports). These obstacles include direct costs generated by policy barriers that limit market entry, but can also include infrastructure deficiencies, geographical location, and institutional capacities, and/or obstacles imposed by regulatory measures. Among the latter obstacles, examples include difficulties in accessing the information necessary to operate in a market, the predictability and stability of the business environment in a market, and the quality of the decision-making process and administrative procedures of competent authorities in the domestic and export markets. The focus of the report is the trade costs confronted by IT and ITeS firms. IT and ITeS operations are the backbone to provide digital services, digital goods and depend on digital technologies, conform an integral part of the overall ecosystem. The report relies on a survey conducted on 782 IT and ITeS firms across different cities. The objective of the survey was to examine the importance of these factors for Pakistani firms and to provide advice to policymakers. To complement the survey results, the main findings were discussed in focus group structured interviews. Firms interviewed covered different services activities beyond software companies and included both exporters (534 firms) and non-exporters (248 firms), reflecting the export competitiveness as well as domestic competitiveness of Pakistan's IT services sector. The analysis aims to improve our understanding of Pakistan's IT performance and the obstacles confronted in this field.